2002
DOI: 10.1007/s10227-001-0157-z
|View full text |Cite
|
Sign up to set email alerts
|

HLA Haplotypes and Class II Molecular Alleles in Argentinian Patients with Pemphigus Vulgaris

Abstract: In patients with the haplotype DRb1* 0402/DQb1* 0302 the affectation of 10%-30% of the corporal surface prevailed (ACS). In patients with DRb1* 1401/DRQb1* 0503, involvement of <10% of the ACS prevailed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
12
0
7

Year Published

2005
2005
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 23 publications
7
12
0
7
Order By: Relevance
“…These findings are consistent with previous genotype analyses of AJ, French, Italian, Sardinian, Spanish, Argentinean, and Iranian populations [12,14,16,22,23,35]. A high occurrence of DRB1*1401 has been reported in those of Japanese [20] and Mediterranean lineage [12,13,15,22], as well as an increase in the DRB1*1404 allele in Chinese [19], Pakistani [21], and French [12] PV patients (Table 1). In the analysis of 32 AJ patients, only DRB1*0402 was significantly overrepresented at the DRB1 locus (Table 2).…”
Section: Hla Allele Associations In Ashkenazi Jewish and Non-jewish Csupporting
confidence: 94%
See 1 more Smart Citation
“…These findings are consistent with previous genotype analyses of AJ, French, Italian, Sardinian, Spanish, Argentinean, and Iranian populations [12,14,16,22,23,35]. A high occurrence of DRB1*1401 has been reported in those of Japanese [20] and Mediterranean lineage [12,13,15,22], as well as an increase in the DRB1*1404 allele in Chinese [19], Pakistani [21], and French [12] PV patients (Table 1). In the analysis of 32 AJ patients, only DRB1*0402 was significantly overrepresented at the DRB1 locus (Table 2).…”
Section: Hla Allele Associations In Ashkenazi Jewish and Non-jewish Csupporting
confidence: 94%
“…However, population studies of patients with PV have clearly shown that there are differences among the most prevalent alleles in various ethnic groups (summarized in Table 1). Nine DRB1 alleles have been associated with PV (DRB1*0402, *0403, *0406, *0802, *0804, *1401, *1404, *1405, *1408) in 11 distinct populations [12][13][14][15][16][17][18][19][20]. Two DQB1 alleles, DQB1*0302 and DQB1*0503, are associated with PV patients across the world as well [12,13,15,19,21].…”
Section: Introductionmentioning
confidence: 99%
“…These findings are consistent with previous genotype analyses of AJ, French, Italian, Sardinian, Spanish, Argentinean, and Iranian populations [12,14,16,22,23,35]. A high occurrence of DRB1*1401 has been reported in those of Japanese [20] and Mediterranean lineage [12,13,15,22], as well as an increase in the DRB1*1404 allele in Chinese [19], Indian [21], Pakistani [18], and French [12] PV patients (Table 1). In the analysis of 32 AJ patients, only DRB1*0402 was significantly overrepresented at the DRB1 locus (Table 2).…”
Section: Hla Allele Associations In Ashkenazi Jewish and Non-jewish Csupporting
confidence: 94%
“…The frequencies of two alleles, DQB1*0503 and 0302, deviated significantly in NJ Caucasian patients from controls (Table 2). DQB1*0302 has been reported in studies of other nonJewish Europeans (French, Italian, Sardinian) [22] and DQB1*0503 has been reported to be overrepresented in patients who are non-Jewish of European descent [18] as well as several other ethnic groups [6,9,12,13,15,19,21,36]. The only significantly elevated allele at the DQB1 locus in AJ patients is 0302 (Table 2), consistent with previous reports.…”
Section: Hla Allele Associations In Ashkenazi Jewish and Non-jewish Csupporting
confidence: 89%
See 1 more Smart Citation